Effect of mannitol injection rate on intracranial pressure (甘露醇静脉推注速度对颅内压的影响) - ZHUANGLI Jingyi (庄丽静怡); ZHANG Qiong (张琼) (中西医结合护理)
Objective To investigate the effect of static pushing speed of mannitol on the intracranial pressure. Methods Totally 70 children with acute intracranial pressure increase were divided into two groups: 35 cases in the control group received routine rate of mannitol injection and 35 cases in the observation group received the slow first and then fast injection of mannitol. The effect of two mannitol injection rates was compared. Results The effective time to response of intracranial pressure reduction in the observation group was slightly longer than that in the control group , but with no significant difference(P > 0. 05). The duration of effective intracranial pressure in the observation group was longer than that in the control group (P < 0. 05), and the incidence of adverse reactions in the observation group was lower than that in the control group (P < 0. 05). Conclusion The fast first and then slow injection of mannitol is helpful to maintain the stability of intracranial pressure and reduce the incidence of adverse reactions caused by the drug. (目的 探讨甘露醇静脉推注对颅内压的影响。方法 采用随机数字表法将70例急性颅内压增高症患儿分为2组, 各30例。对照组患儿静脉注射甘露醇时采用常规推注速度, 观察组采取先慢后快的静脉推注速度, 对比2组应用效果。结果 观察组颅内压降低显效时间长于对照组, 但差异无统计学意义(P＞0. 05)。观察组有效颅内压持续时间长于对照组, 差异有统计学意义(P＜0. 05); 观察组不良反应发生率较对照组低, 差异有统计学意义(P＜0. 05)。结论 采取先慢后快的静脉推注速度更有助于维持颅内压的平稳, 降低由该药物所致的不良反应发生风险。)